2010
DOI: 10.1111/j.1365-2958.2009.07010.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the aspartate chemosensory receptor of Campylobacter jejuni

Abstract: SummaryCampylobacter jejuni is a highly motile bacterium that responds via chemotaxis to environmental stimuli to migrate towards favourable conditions. Previous in silico analysis of the C. jejuni strain NCTC11168 genome sequence identified 10 open reading frames, tlp1-10, that encode putative chemosensory receptors. We describe the characterization of the role and specificity of the Tlp1 chemoreceptor (Cj1506c). In vitro and in vivo models were used to determine if Tlp1 had a role in host colonization. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(146 citation statements)
references
References 70 publications
(138 reference statements)
5
141
0
Order By: Relevance
“…Thus, CheW preferentially binds Tlp4, whereas CheV demonstrates a high affinity to Tlp1, Tlp4, Tlp6 as well as Tlp8 [65,66]. It is possible that this competition is part of a kind of sensory adaptation.…”
Section: Different Mechanisms Of Sensory Adaptationmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, CheW preferentially binds Tlp4, whereas CheV demonstrates a high affinity to Tlp1, Tlp4, Tlp6 as well as Tlp8 [65,66]. It is possible that this competition is part of a kind of sensory adaptation.…”
Section: Different Mechanisms Of Sensory Adaptationmentioning
confidence: 99%
“…Tlp1 (cj1506c), Tlp4 (cj0262c) and Tlp10 (cj0019c) could be demonstrated, in contrast to Tlp7 (cj0951c/ cj0952c or cjj81176-0975) and Tlp9 (cj1189), to be relevant for chicken intestinal colonization since a mutation within the corresponding genes significantly decreased the number of bacteria in the faeces. Interestingly, a transposon insertion in gene Tlp10 (cj0019) did not affect the in vitro motility of the bacterium indicating that the lack of a chemoreceptor is not mandatorily linked to the motility of C. jejuni [65,87]. The in vivo examination of the intestinal pathology induced by C. jejuni was not feasible for decades since an appropriate vertebrate model was not available.…”
Section: The Role Of Chemotaxis In Host Colonization and The Pathogenmentioning
confidence: 99%
See 2 more Smart Citations
“…15 A protein-ligand interaction between Tlp1 peri and L-aspartate, but no other amino acid, was thus identified and was further confirmed by STD NMR spectroscopy. 16 In order to further analyse the role of Tlp1 in chemotactic signal transduction, an isogenic deletion mutant and complemented isogenic strains were constructed using the C. jejuni 11168-O reference strain. Chemotaxis assays (capillary and nutrient depleted) demonstrated that Tlp1 is indeed involved sensing aspartate, as the mutation in the Tlp1 sensory domain coding region resulted in a decreased chemotaxis response towards L-aspartate, while migration of the mutant bacteria towards other known chemoattractants was not affected.…”
Section: Victoria Korolikmentioning
confidence: 99%